Interorganisational collaboration to improve accessibility of diagnostic evaluations for children with a developmental disability - Cloet Eva; Jansen Anna; Leys Mark (SAGE Publishing, 2024)
Introduction: A timely integrated diagnostic and care trajectory for children with a developmental disability may prevent severe problems in later life. In Flanders, Belgium, different types of governmental regulated and subsidised settings offer diagnostic evaluations, as (part of) their mission. However, they operate in a non-coordinated way inducing severe accessibility problems for the public. This article studies the factors impacting on interorganisational collaboration and proposes an interorganisational conceptual model improving accessibility. Methods: Focus groups were performed per type of organisation. Qualitative data were categorised thematically in an iterative process of data- and researcher triangulation. A member check validation was organised. Results: Fifty-nine individuals participated in 6 focus groups. Structural and agency-related barriers for interorganisational collaboration were identified at micro, meso and macro level. Participants provided suggestions for better interorganisational collaboration. Discussion: To improve accessibility adapted to patients' needs, a patient-centred, integrated and interorganisational network model grounded in a stepped care logic is proposed to adapt the current organisation-centred model. Conclusion: A timely, integrated, diagnostic and care trajectory for children with a developmental disability preventing severe problems in later life requires an integration of services during the overall care trajectory of children by means of interorganisational collaboration.